EXTRAPULMONARY TUBERCULOSIS: CLINICAL EPIDEMIOLOGICAL CHARACTERISTICS AND DIAGNOSTICS - I. I. Solonko; G. L. Gurevich; E. M. Skryagina; M. I. Dyusmikeeva (Туберкулез и болезни лёгких)
The objective: to provide clinical and epidemiological characteristics of extrapulmonary tuberculosis and develop simultaneous rapid diagnostics of tuberculosis and drug susceptibility based on molecular genetic and bacteriological tests of non-respiratory samples and resection (tissue) materials. Statistic reports on tuberculosis for 2016 were analyzed, as well as materials of electronic register Tuberculosis in order to assess extrapulmonary tuberculosis incidence and its structure. Surgery was performed in 20 extrapulmonary tuberculosis patients, non-respiratory samples and tissue were obtained in order to isolate DNA of tuberculous mycobacteria. Still, there is a significant number of extrapulmonary tuberculosis patients who remain undetected. On the other side, it is possible to state that there is overdiagnosis of extrapulmonary tuberculosis. The high efficiency of GeneXepert MTB/RIF for testing of resection materials received through surgical treatment of extrapulmonary tuberculosis has been proved. This method allowed detecting DNA of tuberculous mycobacteria in biological specimens fast (within 2 hours) and also testing drug susceptibility to rifampicin. Results of rifampicin susceptibility testing, received by culture and GeneXpert MTB/RIF are compatible. Due to this, it is possible to amend treatment regimens in a timely manner.